On radii of starlikeness and convexity for convolutions of starlike functions - Yi Ling; Shusen Ding (International Journal of Mathematics and Mathematical Sciences)
In this paper, we obtain the radiuses of univalence, starlikeness and convexity for convolutions of starlike functions.